Adaptive Housing Planning Strategy for Post-Disaster - Zuhri, Syaifuddin; Ghozali, Imam (Budapest International Research and Critics University, 2022)
Disasters are a bad condition, especially when these conditions occur in densely populated areas or residential areas, of course this will result in damage to infrastructure, like buildings, houses and other facilities or communities. Of course, this can be of particular concern in the context of the loss or damage to buildings inhabited by the local community. Attention to post-disaster conditions, seen in the context of the availability of houses intended for disaster victims, is of course a major concern. Because the loss or damage to their buildings or homes will have an impact on losing their shelter in this condition. This research tries to develop this problem so that the availability of houses for them can be provided quickly with simple building and construction. The developed building model is very adaptive to the basic needs of the space needed for them to be able to live in the house with the characteristics of a building that is comfortable and safe for them to live in. The development of building field panels that have been developed is very effective and efficient in adapting to the use of lightweight structural systems and materials.